2011
DOI: 10.1111/j.1540-5907.2011.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Mission or Empire, Word or Sword? The Human Capital Legacy in Postcolonial Democratic Development

Abstract: Why are some former colonies more democratic than others? The British Empire has been singled out in the debates on colonialism for its benign influence on democracy. Much of this scholarship has focused on colonialism's institutional legacies; has neglected to distinguish among the actors associated with colonialism; and has been nation‐state focused. Our subnational approach allows us to isolate the democracy effects of key actors operating in colonial domains—Christian missionaries—from those of colonial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(29 citation statements)
references
References 60 publications
1
25
0
1
Order By: Relevance
“…Colonial Protestant missions have been praised for their long-term positive effects on literacy, education, and information. Notably, Woodberry (2004; proposed the 'mission education hypothesis' and provided cross-national evidence of this effect, which was substantiated in sub-national analyses (Lankina & Getachew, 2012;Wietzke, 2012). Further, mission activities have contributed to democratic development by supporting mass printing, newspapers, reforms, the public sphere, and civil society (Cage & Rueda, 2016;Woodberry, 2012).…”
Section: B Instrumental Variable Regression Using Historical Protestamentioning
confidence: 94%
See 1 more Smart Citation
“…Colonial Protestant missions have been praised for their long-term positive effects on literacy, education, and information. Notably, Woodberry (2004; proposed the 'mission education hypothesis' and provided cross-national evidence of this effect, which was substantiated in sub-national analyses (Lankina & Getachew, 2012;Wietzke, 2012). Further, mission activities have contributed to democratic development by supporting mass printing, newspapers, reforms, the public sphere, and civil society (Cage & Rueda, 2016;Woodberry, 2012).…”
Section: B Instrumental Variable Regression Using Historical Protestamentioning
confidence: 94%
“…Second, differences in informational endowments around colonial Protestant missions in Africa have persisted for more than 200 years (Woodberry, 2004(Woodberry, , 2012Gallego & Woodberry, 2010;Nunn, 2009Nunn, , 2016Wantchekon, Klasnja & Novta, 2015). Both cross-and sub-national research (Woodberry, 2004(Woodberry, , 2012Lankina & Getachew, 2012;Wietzke, 2012) has found that groups and areas exposed to Protestant missions have substantially different levels of modern-day literacy, schooling, and human capital than those groups and areas with no exposure to Protestant missions, which is due to intra-household generational transmission and path-dependent local institutional investments (Wietzke, 2012;Huillery, 2009;Lankina & Getachew, 2012: 467).…”
Section: B21 Relevance Of the Instrumentmentioning
confidence: 99%
“…One piece of 'food for thought' that we discuss at the end of the note is whether Woodberry's theoretical mechanisms linking Protestantism to 1 Although Woodberry does not test these relationships quantitatively, there is a large literature that uses sub-national data and better identification and generally supports the claims that he reaches in the historical analysis. See Bai and Kung (2015), Becker and Woessman (2009), Becker et al (2016), Cantoni et al (2018), Chen et al (2018), Mantovanelli (2014), Nunn (2014), Lankina andGetachew (2012), andTusalem (2009). Note that the latter two papers also argue that Protestantism affected democracy (in India; and in around 60 transitional states that attempted to democratize or democratized since the third wave, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Приведенное же описание следует счи-тать упрощенным, хотя оно и позволяет выделить некоторые особенности, свойственные «среднестатистическим» представителям этих научных сообществ. 7 См., например, (Darden, Grzymala-Busse, 2006;Becker, Boeckh et al, 2009;Grosjean, Senik, 2011;Lankina, Getachew, 2012). Журнал НЭА, № 1 (17), 2013, с.…”
unclassified